Effects of Dietary Modified Bazhen on Reproductive Performance, Immunity, Breast Milk Microbes, and Metabolome Characterization of Sows - Geng, Jian; Jin, Weicheng; Hao, Jingyou; Huo, Mohan; Zhang, Yuefeng; Xie, Chunmei; Zhao, Baokai; Li, Yanhua (Frontiers in Microbiology, 2021)
Bazhen is a classic prescription used for the prevention of qi and blood deficiency. The present study aimed to investigate the effects of dietary supplementation with modified Bazhen powder (MBP) on sows during lactation. Forty pure-bred Yorkshire sows on day 100 of gestation were randomly fed a standard diet supplemented with 20 g MBP per sow per day (MBP group) or without (control group) during -14 to 7 days relative to parturition. Results showed that the serum levels of interleukin 2 (IL-2), immunoglobulin A (IgA), and IgG were higher, whereas IL-10 level was lower in sows fed with MBP diet than in controls on day 7 postpartum. A significantly elevated proportion of serum CD4+ T cells and a slight increase in the ratio of CD4+ to CD8+ T cells in the MBP group were also observed. Furthermore, MBP supplementation improved gastrointestinal function of postpartum sows, evidenced by increased levels of motilin, gastrin, and nitric oxide. Ultra high-performance liquid chromatography combined with a quadrupole time of flight and tandem mass spectrometer identified a total of 21 absorbed milk components. 16S rRNA gene amplicon sequencing data revealed that the microbiota diversity of the colostrum and transitional milk in the MBP group was increased. At the genus level, relative abundances of Enterococcus and Anaerostipes were significantly lower in the MBP group on day 0 of lactation. Metabolomic analysis showed that 38 metabolites were upregulated, and 41 metabolites were downregulated in the transitional milk; 31 metabolites were upregulated and 8 metabolites were downregulated in the colostrum in response to MBP. Metabolic pathways, protein digestion and absorption, and biosynthesis of amino acids were enriched in the colostrum and transitional milk. Our findings provide new insights into the beneficial effects of MBP, highlighted by the changes to the microbiota and metabolomic profile of breast milk from sows fed with an MBP-supplemented diet. Thus, MBP should be considered as a potential dietary supplement for lactating sows in pork production.